Current decisions on neoadjuvant chemotherapy for early breast cancer: Experts' experiences in the Netherlands. Issue 12 (December 2018) - Spronk, P.E.R.; de Ligt, K.M.; van Bommel, A.C.M.; Siesling, S.; Smorenburg, C.H.; Vrancken Peeters, M.T.F.D.; ,
Highlights: An accepted indication for NAC is down staging of the tumour to enable BCS (75%). Contradictory, 21% argued that NAC increases the risk of invasive margins. Only 64% routinely recommended NAC when systemic therapy was indicated. WHO status of ≥2 was stated most frequently a reason to refrain from NAC. Abstract: Purpose: To evaluate the opinion of surgical and medical oncologists on neoadjuvant chemotherapy (NAC) for early breast cancer. Methods: Surgical and medical oncologists (N = 292) participating in breast cancer care in the Netherlands were invited for a 20-question survey on the influence of patient, disease, and management related factors on their decisions towards NAC. Results: A total of 138 surgical and medical oncologists from 64 out of 89 different Dutch hospitals completed the survey. NAC was recommended for locally advanced breast cancer (94%) and for downstaging to enable breast conserving surgery (BCS) (75%). Despite willingness to downstage, 64% of clinicians routinely recommended NAC when systemic therapy was indicated preoperatively. Reported reasons to refrain from NAC are comorbidities (68%), age >70 years (52%), and WHO-performance status ≥2 (93%). Opinions on NAC and surgical management were inconclusive; while 75% recommends NAC to enable BCS, some stated that BCS after NAC increases the risk of a non-radical resection (21%), surgical complications (9%) and recurrence of disease (5%). Conclusion: This article emphasizes the need for more consensus among specialists on the indications for NAC in early BC patients. Unambiguous and evidence-based treatment information could improve doctor-patient communication, supporting the patient in chemotherapy timing decision-making.